2020
DOI: 10.1002/pssb.202000257
|View full text |Cite
|
Sign up to set email alerts
|

Photons, Orbital Angular Momentum, and Neutrons

Abstract: A traveling wave or wave packet may possess orbital angular momentum (OAM) in the form of a phase vortex about its propagation axis. These OAM states are a general wave property and exist in single‐particle wave packets, in a beam of unstructured wave packets of particles or in a mixture. OAM states of photons were first created almost 30 years ago. Recently work has been done to create these states with massive particles: electrons and neutrons. OAM waves can be generated by passing an unstructured wave throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…As a result, each individual neutron passing through the interferometer probed only a small off-centered patch of the phase plate and did not exhibit a well-formed phase vortex. These observations raised doubts as to whether the results of this experiment were at all indicative of vortex neutron generation [247,248].…”
Section: Vortex Neutrons and Atomsmentioning
confidence: 81%
“…As a result, each individual neutron passing through the interferometer probed only a small off-centered patch of the phase plate and did not exhibit a well-formed phase vortex. These observations raised doubts as to whether the results of this experiment were at all indicative of vortex neutron generation [247,248].…”
Section: Vortex Neutrons and Atomsmentioning
confidence: 81%
“…Concerning a SPP-induced neutron OAM (n-OAM), experiments with laser light using a SPP have shown that incident wave packets must be able to detect the discontinuity at the center of the vortex phase plate, otherwise the probability of detecting a single particle with uniform OAM around the center of the packet is extremely low [34], which is certainly true for neutrons in a crystal interferometer, and even for X-rays it is difficult to use a division amplitude interferometer (like the used neutron interferometer) to create a vortex wave front with SPP [35].…”
Section: Neutron Crystal Interferometrymentioning
confidence: 99%